Non-Traditional Trademarks in Indonesia: Protection under the Laws and Regulations (An Intellectual Property Law) - Setyawan, Andry; Sulistianingsih, Dewi; Yudistira, Ivan Bhakti (JILS (Journal of Indonesian Legal Studies), 2017)
Non-traditional Trademarks are also known as non-conventional trademarks develop due to business demands. The development of new trademarks like the sound, scent, three dimensions, and the hologram is defined as non-traditional trademarks and non-conventional trademarks of modern trademarks. The international and national regulations of the trademarks are done through several instruments. In Indonesia, they are governed in Act No 20 of 2016 and the regulations of the Ministry of Law and Human Rights No 67 of 2016. Despite their regulations which are accommodated in Act No 20 of 2016, the implementations of the regulation in Indonesia are as well-developed as that of other countries. The problems in the implementation of the non-traditional trademark protection are the responsibilities of the General Directorate of Intellectual Property especially in preparing the facilities and human resources.